Invasive Spartina anglica Greatly Alters the Rates and Pathways of Organic Carbon Oxidation and Associated Microbial Communities in an Intertidal Wetland of the Han River Estuary, Yellow Sea - An, Sung-Uk; Cho, Hyeyoun; Jung, Ui-Jung; Kim, Bomina; Lee, Hyeonji; Hyun, Jung-Ho (Frontiers in Marine Science, 2020)
Biogeochemical process studies and molecular microbiological analyses were applied to assess the effect of invasive Spartina anglica (SA) on organic carbon (Corg) oxidation pathways and microbial community structures in intertidal sediments vegetated by the indigenous marsh plant Suaeda japonica (SJ) and unvegetated mud flats (UMF). Invasive S. anglica possessed 10 times the below-ground biomass of native S. japonica, which was responsible for releasing a substantial amount of labile dissolved organic matter and creating relatively oxidized conditions at the SA site. As a result, microbial metabolic activities measured by rates of anaerobic Corg oxidation, iron reduction (FeR) and sulfate reduction (SR) appeared to be greater at SA site compared with the SJ and UMF sites. SR was the dominant anaerobic respiration pathway at a depth of 0–10 cm for vegetated sediments, but the contribution of FeR to Corg oxidation was exceptionally high in the rhizosphere of the vegetated sites, comprising 60% and 70% of anaerobic Corg oxidation of SA and SJ, respectively. The iron turnover rate at the rhizosphere was 3 times higher at SA site (0.063 d-1) compared with the SJ site (0.023 d-1), indicating that the denser root system of invasive S. anglica greatly accelerates iron cycling. Bacterial communities based on 16S rRNA genes analysis revealed that members in Desulfuromonadaceae related to the reduction of FeOOH and S0 were highly abundant at the relatively oxidized SA site, whereas Desulfobulbaceae, which are known as sulfate reducers, were more dominant at the relatively reduced SJ site. Similarly, two sulfur-oxidizing bacteria groups with different eco-physiological strategies thrived in each of the two vegetated sites. Thioprofundaceae in the Gammaproteobacteria were the predominant S-oxidizers at the less-reduced SA site, whereas Sulfurovum in the Epsilonproteobacteria dominated at the relatively reduced SJ site. Our results suggest that an invasion of tall S. anglica and its subsequent displacement of native S. japonica would greatly alter the biogeochemical C-Fe-S cycles and associated microbial communities, which ultimately generate multidirectional variations in ecological and biogeochemical processes in coastal ecosystems.